Mutational spectrum by phenotype: panel‐based NGS testing of patients with clinical suspicion of RASopathy and children with multiple café‐au‐lait macules. Issue 2 (12th December 2019) - Castellanos, Elisabeth; Rosas, Inma; Negro, Alex; Gel, Bernat; Alibés, Andreu; Baena, Neus; Pineda, Mercè; Pi, Graciela; Pintos, Guillem; Salvador, Hector; Lázaro, Conxi; Blanco, Ignacio; et al.
Abstract: Children with neurofibromatosis type 1 (NF1) may exhibit an incomplete clinical presentation, making difficult to reach a clinical diagnosis. A phenotypic overlap may exist in children with other RASopathies or with other genetic conditions if only multiple café‐au‐lait macules (CALMs) are present. The syndromes that can converge in these inconclusive phenotypes have different clinical courses. In this context, an early genetic testing has been proposed to be clinically useful to manage these patients. We present the validation and implementation into diagnostics of a custom NGS panel (I2HCP, ICO‐IMPPC Hereditary Cancer Panel) for testing patients with a clinical suspicion of a RASopathy (n = 48) and children presenting multiple CALMs (n = 102). We describe the mutational spectrum and the detection rates identified in these two groups of individuals. We identified pathogenic variants in 21 out of 48 patients with clinical suspicion of RASopathy, with mutations in NF1 accounting for 10% of cases. Furthermore, we identified pathogenic mutations mainly in the NF1 gene, but also in SPRED1, in more than 50% of children with multiple CALMs, exhibiting an NF1 mutational spectrum different from a group of clinically diagnosed NF1 patients (n = 80). An NGS panel strategy for the genetic testing of these two phenotype‐defined groups outperforms previous strategies. Abstract : Children with neurofibromatosis type 1 (NF1) may exhibit an incomplete clinical presentation, making difficult to reach a clinical diagnosis. A phenotypic overlap may exist in children with other RASopathies and also with other genetic conditions if only multiple café‐au‐lait macules (CALMs) are present. We present the validation and implementation into diagnostics of a custom NGS panel (I2HCP, ICO‐IMPPC Hereditary Cancer Panel) for testing patients with a clinical suspicion of a RASopathy and children presenting multiple CALMs. We describe the mutational spectrum and the detection rates identified in these two groups of individuals.